Exploring the Lived Spiritual Needs of Individuals with Schizophrenia: A Phenomenological Study Informing Holistic Mental Health Care - Kuncoro, Bambang; Rachmat, Nur; Hidayati, Betty (Chakra Brahmanda Lentera Institute, 2026)
Background: Spirituality has increasingly been recognized as an important dimension of recovery in severe mental illness. However, qualitative understanding of the lived spiritual needs of individuals with schizophrenia remains limited, particularly in Low- and Middle-Income Countries (LMICs). This study aimed to explore the lived spiritual needs of individuals with schizophrenia and examine their significance within recovery-oriented mental health care. Methods: This qualitative study employed van Manen’s interpretive phenomenology grounded in Heideggerian philosophy. Seven participants diagnosed with schizophrenia according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and International Classification of Diseases, Tenth Revision (ICD-10; F20.x) were recruited using purposive sampling. Inclusion criteria included clinical stability, living with family, and the ability to communicate verbally. Exclusion criteria included acute psychotic exacerbation and severe cognitive impairment interfering with communication. Data were collected through face-to-face semi-structured interviews (40–60 minutes; mean 52 minutes), supported by field notes. Data saturation was achieved when no new codes emerged in the final interviews. Data were analyzed using an interpretive phenomenological approach guided by van Manen, supported procedurally by Miles and Huberman’s interactive model for data organization. This study adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results: Three major themes emerged: (1) Transcendence (inner peace, actualization of trust, hope, forgiveness, religious doctrine); (2) Sense of Existence (social support and usefulness); and (3) Personal Values (gratitude and search for meaning). Spirituality functioned as an existential integration mechanism facilitating emotional regulation, identity reconstruction, and recovery-oriented meaning-making. Conclusion: Spiritual needs play a central role in recovery processes among individuals with schizophrenia. Integrating culturally sensitive spiritual assessment into psychiatric services may strengthen holistic and recovery-oriented mental health care in LMIC contexts.